A novel dammarane triterpenoid alleviates atherosclerosis by activating the LXRα pathway - Yan Huang; Xiaodong Ran; Hongmei Liu; Mingming Luo; Yiyu Qin; Jinqiong Yan; Xiaohui Li; Yi Jia (BMC, 2023)
Abstract Background We have previously demonstrated that ginsenoside compound K can attenuate the formation of atherosclerotic lesions. Therefore, ginsenoside compound K has potential for atherosclerosis therapy. How to improve the druggability and enhance the antiatherosclerotic activity of ginsenoside compound K are the core problems in the prevention and treatment of atherosclerosis. CKN is a ginsenoside compound K derivative that was previously reported to have excellent antiatherosclerotic activity in vitro, and we have applied for international patents for it. Methods Male C57BL/6 ApoE−/− mice were fed a high-fat and high-choline diet to induce atherosclerosis and were subjected to in vivo studies. In vitro, the CCK-8 method was applied to evaluate cytotoxicity in macrophages. Foam cells were utilized, and cellular lipid determination was performed for in vitro studies. The area of atherosclerotic plaque and fatty infiltration of the liver were measured by image analysis. Serum lipid and liver function were determined by a seralyzer. Immunofluorescence and western blot analysis were conducted to explore the alterations in the expression levels of lipid efflux-related proteins. Molecular docking, reporter gene experiments and cellular thermal shift assays were used to verify the interaction between CKN and LXRα. Results After confirming the therapeutic effects of CKN, molecular docking, reporter gene experiments and cellular thermal shift assays were used to predict and investigate the antiatherosclerotic mechanisms of CKN. CKN exhibited the greatest potency, with a 60.9% and 48.1% reduction in en face atherosclerotic lesions on the thoracic aorta and brachiocephalic trunk, reduced plasma lipid levels and decreased foam cell levels in the vascular plaque content in HHD-fed ApoE−/− mice. Moreover, CKN in the present study may exert its antiatherosclerotic effects through activated ABCA1 by promoting LXRα nuclear translocation and reducing the adverse effects of LXRα activation. Conclusions Our results revealed that CKN prevented the formation of atherosclerosis in ApoE−/− mice by activating the LXRα pathway.